2017
DOI: 10.1002/2016wr019635
|View full text |Cite
|
Sign up to set email alerts
|

Elemental properties, hydrology, and biology interact to shape concentration‐discharge curves for carbon, nutrients, sediment, and major ions

Abstract: To investigate the prevalence and cause of concentration‐discharge (C‐Q) relationships for carbon, nutrients, major ions, and particulates, we analyzed 40 years of water quality data from 293 monitoring stations in France. Catchments drained diverse landscapes and ranged from 50 to 110,000 km2, together covering nearly half of France. To test for differences during low and high flows, we calculated independent C‐Q slopes above and below the median discharge. We found that 84% of all catchment‐element combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
436
10

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 298 publications
(519 citation statements)
references
References 93 publications
56
436
10
Order By: Relevance
“…This behaviour was mostly confined to NO 3 and may result from dilution of nitrate sources that exhibit extremely stable flow (e.g., Florida's many artesian springs; Heffernan et al, ). This explanation differs from Moatar et al (), who found similar patterns, but suggests that they result from biogeochemical controls. Specifically, they contend that low flows favour biotic NO 3 uptake; but as discharge increases, the uptake velocity dramatically declines, precluding clear impacts on NO 3 flux.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…This behaviour was mostly confined to NO 3 and may result from dilution of nitrate sources that exhibit extremely stable flow (e.g., Florida's many artesian springs; Heffernan et al, ). This explanation differs from Moatar et al (), who found similar patterns, but suggests that they result from biogeochemical controls. Specifically, they contend that low flows favour biotic NO 3 uptake; but as discharge increases, the uptake velocity dramatically declines, precluding clear impacts on NO 3 flux.…”
Section: Discussioncontrasting
confidence: 83%
“…These three properties suggest that regardless of low‐flow solute behaviour, high‐flow behaviour tends towards dilution, with high‐flow similarly defined for all catchments as >50% flow exceedance. The apparent generality of slope breaks at median flow emerges from our synthesis and important recent work (Moatar et al, ). This generality suggests common solute and flow generation processes across divergent watersheds.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Compared to diurnal patterns, storm events induced considerably greater variability in streamflow dynamics and NO 3 -N and DOC concentrations, with no evidence for chemostatic behavior during any events [Moatar et al, 2017]. The rapid response of streamflow to precipitation inputs can be attributed in part to the numerous ditches and tile drains in the upper catchment.…”
Section: Temporal Dynamics Of Streamflow No 3 -N and Docmentioning
confidence: 89%
“…Catchments also integrate geochemical and microbial reactions occurring along a distribution of water flow paths that mobilize, transport, and transform dissolved solutes to stream networks van der Velde et al, 2010]. In-stream processes further alter C-Q-L relationships along the river network, from headwaters to catchment outlet at multiple nested spatiotemporal scales [Bieroza and Heathwaite, 2015;Moatar et al, 2017]. In-stream processes further alter C-Q-L relationships along the river network, from headwaters to catchment outlet at multiple nested spatiotemporal scales [Bieroza and Heathwaite, 2015;Moatar et al, 2017].…”
Section: Introductionmentioning
confidence: 99%